2013
DOI: 10.1007/s00170-013-5320-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of vehicle crash modeling techniques: theory and application

Abstract: Creating a mathematical model of a vehicle crash is a task which involves considerations and analysis of different areas which need to be addressed because of the mathematical complexity of a crash event representation. Therefore, to simplify the analysis and enhance the modeling process, in this work, a brief overview of different vehicle crash modeling methodologies is proposed. The acceleration of a colliding vehicle is measured in its center of gravity-this crash pulse contains detailed information about v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…CRASH) [4,22,28,29]. In some research procedures, advanced signal processing and identification techniques are also used, as for example those based on the wavelet transformation and the NARMA method [18]. An extensive review of those approaches, together with examples of the application of experimental, analytical and simulation results to the analysis and reconstruction of motor vehicle collisions can be found, for example, in [1,10,21].…”
Section: Introductionmentioning
confidence: 99%
“…CRASH) [4,22,28,29]. In some research procedures, advanced signal processing and identification techniques are also used, as for example those based on the wavelet transformation and the NARMA method [18]. An extensive review of those approaches, together with examples of the application of experimental, analytical and simulation results to the analysis and reconstruction of motor vehicle collisions can be found, for example, in [1,10,21].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical models of a viscoelastic body, such as Kelvin-Voigt, Maxwell, and Zener, are widely used in the analysis of crash tests and accident reconstructions; see [5]. Experimental results of a car to pole frontal impact test are presented in the papers of Pawlus et al [6,7]. Numerical simulations obtained by using one viscoelastic body described by some of the standard viscoelastic models, analyzed in the two last mentioned papers, did not show satisfactory agreement with the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of the vehicle during impact can then be simulated by defining values for the spring-and damping coefficients. Although there are several mathematical models in the literature, Pawlus et al [1] showed that the Maxwell model gives great results when compared with experimental crash data. Further, when dealing with LPMs, the spring-and damping coefficients almost certainly will need to be optimized to get satisfactory results.…”
mentioning
confidence: 99%